"Free food on campus!": Using instructional technology to reduce university food waste and student food insecurity. Issue 7 (3rd October 2022) - Frank, Laura B.
Abstract: Objectives As food insecurity among college students in the United States continues to rise, large quantities of food are wasted on college campuses. This paper presents a simple, low-cost approach to address both issues, using an electronic learning management system to connect college students with good quality excess food. Participants: Students at a small East Coast urban university. Methods: Using the MAP-IT framework, a university-wide food rescue system was developed to alert students to obtain food. Results: During the first twelve months of implementation, 451 students enrolled to receive announcements. 78% of students reported satisfaction with the food obtained. Conclusions: This program was successful in providing students with access to desirable food that would otherwise have been wasted.